2018
DOI: 10.5603/ait.2018.0017
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-based assessment of hyomental distances in neutral, ramped, and maximum hyperextended positions, and derived ratios, for the prediction of difficult airway in the obese population: a pilot diagnostic accuracy study

Abstract: Background: Ultrasonography-assessed hyomental distance (HMD) ratio has been found to discriminate between obese patients with Cormack-Lehane grades 1 or 2 vs. those with grades 3 or 4. The aim of our study is to evaluate the performance of the HMD evaluated ultrasonographically in neutral, ramped, and maximum hyperextended positions, as well as for the ratios obtained by dividing the HMD in the ramped position to that in the neutral position (HMDR1) and by dividing the HMD in maximum hyperextension to that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 21 publications
3
64
0
Order By: Relevance
“…Firstly, in our study, all participants were cervical spondylosis patients with abnormal lower cervical spines below hyoid level and usually there was no signi cant difference in the upper cervical spines. The median of HMDR in the easy laryngoscopy group was 1.21 which was smaller than the median of HMDR (1.34) in the study by Petrisor et al However, the median of HMDR in the di cult laryngoscopy group was 1.22 which was in accordance with the median of HMDR (1.21) in the study by Petrisor et al [18]. Secondly, the HMDR measured by ultrasound in other studies could not eliminate the in uence of soft tissue on the indicator measurement.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Firstly, in our study, all participants were cervical spondylosis patients with abnormal lower cervical spines below hyoid level and usually there was no signi cant difference in the upper cervical spines. The median of HMDR in the easy laryngoscopy group was 1.21 which was smaller than the median of HMDR (1.34) in the study by Petrisor et al However, the median of HMDR in the di cult laryngoscopy group was 1.22 which was in accordance with the median of HMDR (1.21) in the study by Petrisor et al [18]. Secondly, the HMDR measured by ultrasound in other studies could not eliminate the in uence of soft tissue on the indicator measurement.…”
Section: Discussionsupporting
confidence: 64%
“…HMD is measured between the anterior border of the chin and the anterior border of the hyoid [17]. In the study by Petrisor et al [18], HMDR seemed to have superior diagnostic accuracy with a cut-off value of 1.23 provides 100% (39.8-100.0) sensitivity and 90.5% (69.6-98.8) speci city for the prediction of di cult airway in the obese population.…”
Section: Discussionmentioning
confidence: 97%
“…A similar study conducted on obese patients, but from a different geographical population, did not confirm this method and could not differentiate the patients with easy versus difficult intubation [14]. In a pilot study we conducted on 25 morbidly obese patients, the sensitivity and specificity of the method were 75% [23].…”
Section: Anterior Neck Soft Tissue Thicknessmentioning
confidence: 84%
“…Because of the wide variability in clinical studies, ultrasound evaluation of the HMDR might be of interest, especially that the scanning technique is simple. With a cutoff of 1.24, the sensitivity of ultrasound-measured HMDR was 86-100%, while the specificity was 72-90.5% in the non-obese and obese populations [10,11]. Using ROC analysis, Koundal et al found a cutoff of 1.08-1.085 for HMDR echo , with 65-75% sensitivity and 77-85% specificity [9,12].…”
Section: Imaging Studiesmentioning
confidence: 99%
“…The diagnostic accuracy of this parameter varied widely in subsequent studies, suggesting that evaluation of clinical parameters might be operator-dependent or that there might be difficulties regarding the palpation of the hyoid bone in certain patients [4][5][6][7][8]. In the last years, ultrasound measurements were applied for the hyomental distance ratio (HMDR echo ), also with variable sensitivity and specificity [9][10][11][12][13]. However, until now, each of the previous studies on HMDR focused on a single technique of measurement, either clinical or ultrasonographical, and no study compared the two.…”
Section: Introductionmentioning
confidence: 99%